Particularities of allergy in the Tropics. Issue 1 (December 2016) - Caraballo, Luis; Zakzuk, Josefina; Lee, Bee; Acevedo, Nathalie; Soh, Jian; Sánchez-Borges, Mario; Hossny, Elham; García, Elizabeth; Rosario, Nelson; Ansotegui, Ignacio; Puerta, Leonardo; Sánchez, Jorge; et al.
Abstract Allergic diseases are distributed worldwide and their risk factors and triggers vary according to geographical and socioeconomic conditions. Allergies are frequent in the Tropics but aspects of their prevalence, natural history, risk factors, sensitizers and triggers are not well defined and some are expected to be different from those in temperate zone countries. The aim of this review is to investigate if allergic diseases in the Tropics have particularities that deserve special attention for research and clinical practice. Such information will help to form a better understanding of the pathogenesis, diagnosis and management of allergic diseases in the Tropics. As expected, we found particularities in the Tropics that merit further study because they strongly affect the natural history of common allergic diseases; most of them related to climate conditions that favor permanent exposure to mite allergens, helminth infections and stinging insects. In addition, we detected several unmet needs in important areas which should be investigated and solved by collaborative efforts led by the emergent research groups on allergy from tropical countries.